Enhancement of ozonation using microbubbles – Micropollutant removal, mass transfer and bromate formation - John, Alexander; Carra, Irene; Jefferson, Bruce; Bertolaso, Lucie; Brookes, Adam; Jarvis, Peter (Elsevier, 2024)
Microbubble technology is a promising development in the optimisation of gas–liquid contacting processes. When applied to ozonation, microbubbles have demonstrated significant enhancements to mass transfer, dissolved ozone residual and the speed and extent of compound removal. However, the mechanism by which microbubbles enhance performance over conventional bubbles is not well understood and numerous explanations exist within the literature. To elucidate the critical components that drive such enhancements the performance of microbubbles (Sauter mean diameter 37 µm) and conventional bubbles (5.4 mm) were compared under identical conditions in terms volumetric mass transfer coefficient, steady state dissolved ozone concentration, rate constant for ozone self-decomposition and the rate constant for degradation of two pesticides: mecoprop and metaldehyde. Overall, the improvement observed in performance can be attributed to the increase in the volumetric mass transfer coefficient through the combination of an increase in specific interfacial area and a decrease in the mass transfer coefficient. The increase in area outweighed the decrease in mass transfer coefficient such that an overall improvement factor of 1.6 was observed for microbubbles over conventional bubbles. All other differences were an artefact of the enhanced mass transfer leading to higher dissolved ozone concentrations when operating at a fixed input dose. For the first time it has been shown that when normalised to the amount of ozone transferred to the water, no enhancement in hydroxyl radical production, bromate formation or impact from the background constituents could be observed.
Keywords: Microbubbles; Pesticides; Ozonation; Drinking water; Mass transfer